Analysis of regional government food reserves in West Java Province. Issue 1 (November 2021) - Agustian, A; Darwis, V; Muslim, C; Sunarsih,; Septanti, K S; Aldillah, R; Swastika, D K S; Suryana, A
Abstract: The Law No. 18/2012 concerning food mentions that local governments determine the types and amounts of certain food reserves. Currently, the existence of regional government food reserve (RGFR) is still relatively varied, according to the capacity of local governments. This study aims to analyze management policies, the amount of RGFR, management problems and strengthening strategies. The research was conducted in March-April 2021 in Cianjur and Garut Districts, West Java Province. The analysis was carried out quantitatively and descriptive qualitatively. The results of the analysis show that the RGFR management policy in West Java is stipulated by Governor Regulation No. 37/2017 concerning the provision and distribution of RGFR, while in the study location the stipulation is through a Regent Regulation. In West Java, RGFR management collaborates with BULOG, with a RGFR amount target of around 1, 200 tons (2020). At the study locations in Garut and Cianjur Districts, the amount of district government food reserves (DGFR) in 2020 was 50 tons and 33 tons, respectively. In Garut District, food procurement through third party partners and the district government already has a food storage warehouse, while in Cianjur District the management is in collaboration with BULOG. The problems in RGFR management, among others, are related to the capacity of the budget for food procurement, and the seriousness of local governments to increase it. To strengthen RGFR and DGFR, government policy support is needed to increase food production according to regional production potential, and continuously increase the amount and continue to improve the management system.